Tethered swimming and dry land force parameters: useful tools to characterize front crawl performance in both genders - Morouço, Pedro Gil Frade (2014)
The major purpose of this work was to examine possible relationships between tethered forces and dry-land exercises with swimming performance, for both males and female swimmers. Additionally, it was intended to verify if tethered swimming could be an easy, operative and accurate methodology for the biophysical evaluation of swimmers. For the accomplishment of these purposes the following sequence was used: (i) reviewing available literature; (ii) comparison of tethered swimming with free swimming; (iii) analyzing variables and relationships obtained in tethered swimming and dry-land strength tests with swimming performance; (iv) assessing front crawl arm (a)symmetries through tethered swimming; (v) and indentifying the relative contribution of arms and legs for whole-body tethered forces. Results suggest that: (i) tethered swimming does not alter stroke rate, blood lactate concentrations, heart rate and perceived exertion when compared to free swimming of equal duration; (ii) the relationship between maximum force and swimming velocity is non-linear, whereas with impulse is linear; (iii) power assessed in dry-land strength exercises seems to be a more accurate parameter than maximum load; (iv) for boys lat pull down, and for girls squat, are the most related dryland exercises with swimming performance; (v) tethered swimming can be a simple, low cost and time saving methodology in terms of whole-body coordination and arm stroke (a)symmetries evaluation; (vi) the leg-kicking represents a higher role for all body propulsion than assumed; (vii) swimmers present asymmetries within arms force production that tend to decrease along a maximal effort.